2012
DOI: 10.5005/jp-journals-10024-1196
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Occlusion during Eccentric Mandibular Movements in Young Adults

Abstract: Bolton's original data does not represent Indian population. In our study greater size variability was found in maxillary teeth as compared with mandibular teeth except mandibular first molar. Our study indicated that population-specific standards are necessary for clinical assessments. Significant differences were shown for the overall ratio and anterior ratio for both sexes as compared to Bolton's ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
9
0
8
Order By: Relevance
“…The Japanese-Brazilian group showed significantly greater anterior and overall ratios than Bolton standards. Other studies also reported significantly greater anterior ratio 8,7,13,24 and overall ratio 6,13,25 than Bolton standards for different populations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The Japanese-Brazilian group showed significantly greater anterior and overall ratios than Bolton standards. Other studies also reported significantly greater anterior ratio 8,7,13,24 and overall ratio 6,13,25 than Bolton standards for different populations.…”
Section: Discussionmentioning
confidence: 82%
“…Although some studies report that Bolton's ratios can be applied for different populations 10,11 , others claim the opposite 6-8,12,13 . Smith et al 13 (2014) also found significant differences for the anterior and overall ratios compared to Bolton's ratios in an Indian population. These studies highlight the need for population-specific standards for clinical assessments of tooth size ratios.…”
Section: XXmentioning
confidence: 93%
“…Pro mnohé autory není otázka okluzních kontaktů při protruzním pohybu zajímavá, spíše se zabývají okluzními kontakty při pohybu laterotruzním, a tak tato oblast trpí nedostatkem nejen epidemiologických dat. Protruzní kontakty zkoumali Scaife a Holt [11], Gazit a Lieberman [4], Sadowsky a BeGole [9], Sadowsky a Polson [10], Ingervall, Hähner a Kessi [5], Al-Nimri, Bataneih, Abo-Farha [1], Sreekumar, Rupesh, Pradeep [12]. Někteří z nich okluzní kontakty také klasifikovali.…”
Section: Abstract: Occlusal Contacts -Occlusal Interferences -Occlusiunclassified
“…Účastníky této studie byli mladí dospělí jedinci s dobře zachovalým chrupem. Kritéria, která museli splnit, aby mohli být zařazeni do studie, nebyla tak přísná jako u některých jiných studií [1,12]. Naše kritéria byla relativně volná, tak jako u dalších studií [5,11].…”
Section: Diskuseunclassified
“…The Bolton analysis is the ratio between the mesiodistal number of maxillary and lower teeth that has been used extensively in detecting interarch dental discrepancies [10][11][12]. The Bolton analysis is divided into two, namely the anterior Bolton ratio and the overall Bolton ratio [13].…”
Section: Introductionmentioning
confidence: 99%